The government spending on human development in driving economic growth: A systematic literature review of ASEAN countries - Jefri , Muhammad Taufik; Chee Ann , Lim (Journal of Islamic, Social, Economics and Development, 2025)
Although research on economic growth in ASEAN is increasing, there is a lack of in-depth analysis that connects government spending on human development with sustained economic performance. Most existing studies tend to focus on education, health, and social sectors separately, without considering their combined impact on growth. This study aims to comprehensively review the empirical literature on the effects of government spending on education and health on human development, which in turn influences economic growth in ASEAN countries. A literature search was conducted using Scopus and Web of Science databases for articles published between 2015 and 2025. Relevant studies were selected based on specific inclusion and exclusion criteria, and key data were extracted and analyzed thematically. The findings suggest that strategic spending in human development, particularly in education and health, is strongly and positively linked to economic growth, although results vary depending on country policy contexts. This review contributes to the literature by providing a structured synthesis of existing evidence and laying the groundwork for future empirical and policy-driven research.